YOUNG PRECARPATHIAN SCHOLARS: A REVIEW OF RESEARCH WORKS - Oleksii Vorobets (Vasyl Stefanyk Precarpathian National University, 2015)
The article presents a review of scientific papers, monographic researches in humanities that were written under the guidance of leading scientists at the Vasyl Stefanyk Precarpatian National University.